Mucormycosis during Coronavirus Disease pandemic: A diagnosis we cannot afford to miss - Kaneesh Karthik Arthanari; Sivakumar Annamalai; Arthiie Thangavelu; Chandrika Palanivelu; Gowtham Suresh; Sambavi Anbuselvan (Wolters Kluwer Medknow Publications, 2021)
Mucormycosis is a very aggressive, devastating opportunistic fungal infection commonly involving nasal, maxillary,orbital, and cerebral regions. In the second wave of the coronavirus disease 2019 (COVID-19) pandemic, a high frequency of mucormycosis infections has been seen because of the triad of COVID-19, systemic steroids, and preexisting diabetes mellitus. A patient might present with a simple mobile tooth/teeth with multiple gingival abscesses Necrotic bone could be seen in the palate. Blackish discoloration might be present in the oral mucosa. There might be extraoral swelling . If rhino-oculo cerebral mucormycosis is diagnosed, then there are two immediate treatment modalities to be followed. Both surgical and medical treatment are necessary. Surgical is thorough debridement of the necrotic tissue. To prevent the occurrence of mucormycosis, meticulous glycemic control and rational use of steroids and antibiotics for the shortest possible time with adequate attention toward the ventilators and tubing are necessary.